KARAKTERISTIK LUKA PADA KORBAN KECELAKAAN LALU LINTAS DI INSTALASI KEDOKTERAN FORENSIK RSUP SANGLAH DENPASAR BALI 2012 - Agung Adi Nugroho; Kunthi Yulianti (E-Jurnal Medika Udayana, 2016)
CHARACTERISTIC OF INJURY IN TRAFFIC ACCIDENT VICTIMS AT FORENSIC DEPARTEMENT OF SANGLAH HOSPITAL DENPASAR BALI 2012 ABSTRACT Introduction: Traffic accidents definines as accidents happen in highway which involves the use of roads for transportation either by the non-motorized vehicles users or the motor vehicle user. The Number of accidents in Bali on 2012 was 2730 with the number of death reached approximately 594 people, and of 1299 were severely injured and the rest suffered only minor injuries. In this study we want to evaluate characteristic of injury in traffic accident victimsat Forensic departement Sanglah Hospital. This study was descriptive cross - sectional study using secondary data. The variables studied were sex, age , injury patterns, and types of vehicles. From this study in 2012 found there were 197 cases of deaths caused by traffic accidents, with most of victims were male (146 cases), dominant age group was young adult age 20-30 years (57 cases). Injurry pattern was found scratched injury 192 cases (97.4% ) ,bruised injury 159 cases (80.7%), open injury 116 cases (58.8 %) cases, bone fractures 98 cases (49.7 %). Accidents mostly involved motor bike, 87 cases (44,6 %). This results were conjuction with national and global study’s findings. Male, Young age and motor bike were risk factors for tarffic accident occurance. Scratched injry was the most common injury found and accident mostly involved motor bike. Futher study about the cause of traffic accident is the needed and we argue the important of socialization and stric traffic law enforcement by government to reduce the number of traffic accident.